1980
DOI: 10.1038/ki.1980.12
|View full text |Cite
|
Sign up to set email alerts
|

Renal disease in familial dysautonomia

Abstract: A study of renal disease in familial dysautonomia identified excess glomerulosclerosis in 10 or 13 autopsied and biopsied patients. Sympathetic nerve terminals could not be found on renal vessels in biopsied tissue; they were invariably demonstrable in controls. Altered renovascular responsivity to systemic hypotension in familial dysautonomia may lead to ischemia and subsequent sclerosis of glomeruli. Review of 79 living outpatients showed that clinically overt renal disease was rare in familial dysautonomia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 18 publications
1
28
1
Order By: Relevance
“…Many of the down-regulated genes participate in cell migration and survival, and this may explain neuropathological findings such as diminished numbers of small nerve fibers and neuronal loss in dorsal root ganglia [3]. The decrease in sympathetic neuronal innervation in FD seems to be pervasive, involving the skin [4], renal blood vessels [5], and the heart (unpublished observations).…”
Section: Hhs Public Accessmentioning
confidence: 99%
“…Many of the down-regulated genes participate in cell migration and survival, and this may explain neuropathological findings such as diminished numbers of small nerve fibers and neuronal loss in dorsal root ganglia [3]. The decrease in sympathetic neuronal innervation in FD seems to be pervasive, involving the skin [4], renal blood vessels [5], and the heart (unpublished observations).…”
Section: Hhs Public Accessmentioning
confidence: 99%
“…Previous studies described diminished sympathetic neuronal populations in biopsies of renal blood vessels and sural nerve [15,16], and decreased numbers of neurons in sympathetic ganglia harvested post-mortem. Note decreased radioactivity in FD at all time points, compared to untreated control subjects, with more rapid decline in radioactivity in the FD group compared to both untreated and desipramine-treated control subjects Consistent with decreased numbers of cardiac sympathetic neurons, at all time points after injection of the sympathetic neuroimaging agent (6-[ 18 F]fluorodopamine) myocardial concentrations of 6-[ 18 F]fluorodopamine-derived radioactivity were decreased by about 25% in the interventricular septum and about 30% in the left ventricular free wall, compared to values in untreated control subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Post-mortem or biopsy studies have indicated that, rather than autonomic failure in FD reflecting dopamine-beta-hydroxylase deficiency, FD entails decreased numbers of sympathetic neurons. Blood vessels in renal and sural nerve biopsy tissue from FD patients have reduced sympathetic terminals [15,16], and sympathetic ganglia contain decreased numbers of neurons [17].…”
mentioning
confidence: 99%
“…Renal insufficiency and need for dialysis are potential complications for the adult FD patient [18]. Patients were divided into those with or without evidence of renal insufficiency based on a serum creatinine of 2 mg% or greater.…”
Section: Assessing Long-term Effectsmentioning
confidence: 99%